2017
DOI: 10.1101/106419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medial prefrontal cortical NMDA receptors regulate depression-like behavior and dictate limbic thalamus innervation

Abstract: Depression is a pervasive and debilitating neuropsychiatric disorder. A single, low dose of the NMDA receptor (NMDAR) antagonist ketamine elicits a long-lasting antidepressant response in patients with treatment-resistant major depressive disorder. Developing mechanistic understanding of how NMDAR antagonism alters synapse and circuit function is pivotal to developing translatable, circuit-based therapies for depression. Here using viral vectors, anatomical tracing, fMRI, and optogenetic-assisted circuit analy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Another experiment confirmed that optogenetic activation of DA neurons in DRN could increase social preference as well ( 88 ). Projections originating from mPFC to different parts of thalamus are also demonstrated to regulate certain aspects of social behavior ( 89 91 ).…”
Section: Optogenetic Findings In Depressive-like Behaviorsmentioning
confidence: 99%
“…Another experiment confirmed that optogenetic activation of DA neurons in DRN could increase social preference as well ( 88 ). Projections originating from mPFC to different parts of thalamus are also demonstrated to regulate certain aspects of social behavior ( 89 91 ).…”
Section: Optogenetic Findings In Depressive-like Behaviorsmentioning
confidence: 99%